Single Roller-to-Cam Indexing Mechanisms Providing Two Maximized Dwells: Determination of Cam Pitch Profile for Optimal Designs - Tripathi K.S. (My University, 2025)
The view point of present research paper is concentrated on a part of a systematic scientific investigation of the mechanical possibilities of generating non-uniform full-rotational output motion with intermittent motion as the most important special case. The paper develops a geometrical construction of the cam pitch profile for optimal designs for single roller-to-cam indexing mechanism providing either two unequal maximum extent dwells with equal indexing angles (and unequal indexing periods) or two equal maximized dwells with unequal indexing angles (and equal indexing periods). Placement of the two dwells in the same half of the motion cycle gives very small periods; very high accelerations; and poor radius of curvature in the transition portion. Hence this paper considers optimal motion diagrams for the case of two dwells placed in different halves of the motion cycle and using the principle of kinematic inversion with intuitive conviction very tactically determines the cam pitch profile. © 2014, The Institution of Engineers (India).